Consider a random sample of size $n$ from a population with pmf $ P(X=x)=\frac{1}{\theta} $ for $x\in \{1,2,..., \theta\}$. I need to show that $Y=X_{(n)}$ is complete sufficient where $X_{(n)}$ is the largest order statistic.

$ P(Y=y)=P(Y \le y)- P(Y \le y-1) = P(X \le y)^n - P(X \le y-1)^n = \left( \frac{y}{\theta} \right)^n - \left( \frac{y-1}{\theta} \right)^n = \dfrac{y^n - (y-1)^n}{\theta ^n}$.

Also the sample pmf is $ P(\mathbf X=\mathbf x) = \dfrac{1}{\theta ^n} $ and since $ \frac{P(\mathbf X=\mathbf x) }{P(Y=y)}$ is independent of $\theta$ then this means that $Y$ is sufficient for $\theta$.

Now to show that if $Y$ is complete then for any measurable function $g(y)$ such that $Eg(y)=0$ for any $\theta$ implys that $g=0$ almost surely.

$0= Eg(y) = \sum_{y=1}^{\theta}g(y)\frac{1}{\theta ^n}(y^n - (y-1)^n )\Rightarrow \sum_{y=1}^{\theta}g(y)(y^n - (y-1)^n)=0$ . If we let $g(1)=1$ and $g(2)=-\frac{1}{2^n-1}$ and $ g(y)=0 $ for each $y\ge 3$ then the $Eg(y)=0$ but $g$ is not $0$ almost surely. So this would mean that $Y$ is not complete but Im assuming im doing something wrong here since the problem is telling me that $Y$ is complete and that I need to show that. Any help is appreciated


In your example, $E(g(Y))\ne 0 $ for $\theta = 1.$

If $E(g(Y)) =0$ then we have $$ \frac{1}{\theta^n}\sum_{i=1}^\theta g(y)(y^n-(y-1)^n)=0.$$ If this is true for all $\theta,$ then the $\theta=1$ case implies $ g(1) = 0.$ Then do the $\theta=2$ case, etc.

| cite | improve this answer | |
  • $\begingroup$ I dont see how my example doesnt work. If $\theta =1$ then we have $\sum_{i=1}^\theta g(y)(y^n-(y-1)^n)=0$. If we let $g(1)=1$ and $g(2)=−\frac{1}{2^n−1}$ and $g(y)=0$ for each $y \ge 3$ then $\sum_{i=1}^\theta g(y)(y^n-(y-1)^n)=1+(−\frac{1}{2^n−1})(2^n−1)+0+0+...+0=1-1=0$. Am I missing something? $\endgroup$ – alpastor Mar 5 '17 at 0:33
  • 1
    $\begingroup$ @n.e. if $\theta = 1$ then $y$ can't be $2$ and there is only one term in the sum. You have $E(g(Y)) = g(1) = 1.$ $\endgroup$ – spaceisdarkgreen Mar 5 '17 at 0:38
  • $\begingroup$ Ohhhh, I didnt take the support of the pmf into consideration, thanks for the help! $\endgroup$ – alpastor Mar 5 '17 at 0:39
  • 2
    $\begingroup$ @n.e. No prob. You took the support into account when you wrote the sum defining the expectation value down correctly. For $\theta = 1$ it reads $0 = \sum_{i=1}^1g(y)(y^n-y^{n-1}) = g(1)$ $\endgroup$ – spaceisdarkgreen Mar 5 '17 at 0:44

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.